Kosovo : Gearing Policies toward Growth and Development - Moalla-Fetini, Rakia (International Monetary Fund, 2005)
This report builds on two previous similar reports from 2001 and 2002-Kosovo: Macroeconomic Issues and Fiscal Sustainability (2001) and Kosovo: Institutions and Policies for Reconstruction and Growth (2002). It is based on work performed during four IMF staff visits spanning a 15-month period from January 2003 to March 2004. The analysis and recommendations of this book contribute to informing the debate about economic policies, in particular, and about the broader issues that will shape Kosovo's future.